Istota i dylematy funkcjonowania Bankowego Funduszu Gwarancyjnego w kontekście stabilności systemu bankowego - Czechowska, Iwona Dorota (Annales. Etyka w Życiu Gospodarczym, 2012)
System guarantying deposits in Poland was created during the economy transformation. Its founding was resulted from a tough situation in the bank sector, that is why it was supposed to be an antidotum to clients' problems connected with solvency of the collapsing banks and also with adjusting to the European community law. The aim of this work is to present The Bank Guarantee Fund, an institution belonging to a network of financial security, which main task is to protect the deponent’s interests and to secure the banking system's stability. The work concerns some aspects of the growing interest in insurance systems for banks deposits and revived discussions on this subject during crisis on bank markets. In reply on the crisis, which was started on credit market subprime in USA and then spread on other segments of financial markets in other countries, the ECOFIN took a decision for increasing the obligatory guarantee limits for individual persons and also for accelerating the payment of guaranteed means. The aim of above changes is to increase surety of clients and trust to bank sector.